Incidence of Type 2 Diabetes Among Patients Exposed to the Combination of Pravastatin and Paroxetine - M. Gooden, Kyna; B. Bibeau, Kristen; Wood, Jennifer; C. Irizarry, Michael; Pan, Xianying; Allen, Jeffery; Sampson, Tim; Heim, Jean-Marie (Current Drug Safety, 2015)
Purpose: This study evaluated the effects of concomitant pravastatin and paroxetine use on the incidence of Type 2 Diabetes Mellitus (T2DM). Methods: A new-user retrospective cohort design was employed using data selected from US health insurance claims databases (OptumInsight and MarketScan) between July 1, 2002, and December 31, 2009. Patients included were of age ≥18; newly prescribed pravastatin or paroxetine; and enrolled in the database for ≥180 days prior to the index date (i.e., first prescription of incident drug). Patients were assigned to either incident pravastatin or incident paroxetine user groups. Patients were followed until the study endpoint (T2DM), discontinuation of incident drug, second drug, or end of study/patient data. Cox proportional hazards models compared T2DM in users of pravastatin who were also taking paroxetine at index the date (combination users) versus pravastatinonly users. A similar analysis among users of paroxetine evaluated the use or non-use of pravastatin at index date. Results: OptumInsight yielded 288,678 incident users of pravastatin or paroxetine; 443,137 were identified in MarketScan. The risk of T2DM among combination users compared to incident pravastatin only users was 1.05 (95% CI: 0.76, 1.44) and 0.94 (95% CI: 0.90, 0.97) in OptumInsight and MarketScan, respectively. The risk of T2DM among combination users compared to incident paroxetine only users was 1.03 (95% CI: 0.69, 1.54) in OptumInsight and 1.02 (95% CI: 0.97, 1.07) in MarketScan. Conclusion: The results indicate no increase in the risk of T2DM due to combined use of pravastatin and paroxetine compared to individual use of the two drugs; however, this study is limited by short mean follow-up.
Keywords: new users design